Model the Solvent-Excluded Surface of 3D Protein Molecular Structures Using Geometric PDE-Based Level-Set Method (Communications in Computational Physics, 2009)
This paper presents an approach to model the solvent-excluded surface (SES)of 3D protein molecular structures using the geometric PDE-based level-set method.The level-set method embeds the shape of 3D molecular objects as an isosurface orlevel set corresponding to some isovalue of a scattered dense scalar field, which issaved as a discretely-sampled, rectilinear grid, i.e., a volumetric grid. Our level-setmodel is described as a class of tri-cubic tensor product B-spline implicit surface withcontrol point values that are the signed distance function. The geometric PDE is evolvedin the discrete volume. The geometric PDE we use is the mean curvature specifiedflow, which coincides with the definition of the SES and is geometrically intrinsic. Thetechnique of speeding up is achieved by use of the narrow band strategy incorporatedwith a good initial approximate construction for the SES. We get a very desirable approximatesurface for the SES.